2008
DOI: 10.1111/j.1538-7836.2008.03024.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed adverse vascular events after splenectomy in hereditary spherocytosis

Abstract: To cite this article: Schilling RF, Gangnon RE, Traver MI. Delayed adverse vascular events after splenectomy in hereditary spherocytosis. J Thromb Haemost 2008; 6: 1289-95.Summary. Background: It is probable that the variety and frequency of delayed adverse vascular events after splenectomy are underappreciated. Splenectomy is performed for a wide variety of conditions, and delayed postsplenectomy hazards are not often studied. Objective: To estimate the relative risk of adverse vascular events in members of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 78 publications
2
65
0
4
Order By: Relevance
“…According to Schilling, splenectomized patients suffering from hereditary spherocytosis (HS) are seven times more likely to suffer an arterial event and three times more likely to undergo a venous event when comparing them to HS patients who had their spleen preserved (22).…”
Section: Vascular Complicationsmentioning
confidence: 99%
“…According to Schilling, splenectomized patients suffering from hereditary spherocytosis (HS) are seven times more likely to suffer an arterial event and three times more likely to undergo a venous event when comparing them to HS patients who had their spleen preserved (22).…”
Section: Vascular Complicationsmentioning
confidence: 99%
“…Indeed, intravascular hemolysis has been linked to pulmonary hypertension (19,24,26,45,59), systemic vasculopathies (27,28,50,52,53,60), and cardiovascular complications (11,25,30,39). Although such studies have suggested that CF-Hb likely plays important roles in vascular disease, the actual contribution of CF-Hb to disease pathology has drawn controversy, particularly in sickle cell disease (SCD) (9,18).…”
mentioning
confidence: 99%
“…[5][6][7][8] However, spleen removal is associated with loss of important physiological functions: splenectomized patients are exposed to long-term complications including infectious risks (particularly high in children under 6 years of age 9 ) and vascular risks. 10,11 To preserve the spleen function, subtotal splenectomy (STS) has been proposed as an alternative to TS. We and others published reports regarding a series of HS patients who underwent STS and showed that it reduced the hemolytic rate and increased the red cell life span while maintaining efficient splenic phagocytic function.…”
mentioning
confidence: 99%